Screening of functional genes affecting the quality of translucent eggshell membranes based on RNA-seq analysis and DIA proteomics - Han, Chun-Hao; Zhao, Xiao-Yu; Wang, Chuan-Wen; Xu, Li-Jun; Liu, Hua-Ge; Chen, Hui; Zhou, Rong-Yan; Wang, De-He (Frontiers in Veterinary Science, 2025)
The quality of eggshells holds substantial economic significance and serves as a critical selection criterion in poultry breeding. Eggshell translucency significantly impairs their aesthetic quality, which is structurally attributed to the thinning of the eggshell membrane or reduced tensile strength. In this study, 836 dwarf white hens were selected, with 45 hens each assigned to the opaque group and the translucent group. Grading for eggshell translucency was conducted at 75, 80, and 85 weeks of age. Based on the results from these three gradings, 35 hens that consistently produced translucent eggs and 35 hens that consistently produced opaque eggs were reclassified into the translucent group and the opaque group, respectively. The thickness of the eggshell membrane, latitudinal and longitudinal tensile force and length, and other indicators related to eggshell membrane quality were measured. Correlation analysis was performed using RNA-seq genomics and DIA proteomics based on the relationships among these indicators. Transcriptome analysis revealed 179 significantly differentially expressed genes, indicating that the causes of translucent eggshells are associated with metabolism, signal transduction, the immune system, molecular binding, transport, and catabolism. Seven potential candidate genes, including CACNA2D2 and KIF26A, were identified. Proteomics analysis identified 565 differentially expressed proteins, suggesting that the expression of eggshell membrane proteins in translucent eggs is linked to protein metabolism, amino acid synthesis, immune regulation, metabolism and oxidative stress, catalytic activity, and molecular transport. Candidate proteins such as SLC4A1, APOA1, and APOA4 were also identified. Combined proteomics and transcriptomics analysis identified 42 differentially expressed proteins and genes, including candidate genes such as CA2, LUZP2, OVA, OVALY, OVST, and AVBD11. This study provides a foundation for elucidating the genetic regulatory mechanisms underlying eggshell membrane quality and offers valuable references and directions for further enhancing eggshell quality.